Optimal asymptotic precision bounds for nonlinear quantum metrology under collective dephasing - Francisco Riberi; Lorenza Viola (APL Quantum, 2025)
Interactions among sensors can provide, in addition to entanglement, an important resource for boosting the precision in quantum estimation protocols. Dephasing noise, however, remains a leading source of decoherence in state-of-the-art quantum sensing platforms. We analyze the impact of classical collective dephasing with arbitrary temporal correlations on the performance of generalized Ramsey interferometry protocols with quadratic encoding of a target frequency parameter. The optimal asymptotic precision bounds are derived for both product coherent spin states and a class of experimentally relevant entangled spin-squeezed states of N qubit sensors. While, as in linear metrology, entanglement offers no advantage if the noise is Markovian, a precision scaling of N−1 is reachable with classical input states in the quadratic setting, which is improved to N−5/4 when temporal correlations are present and the Zeno regime is accessible. The use of nonclassical spin-squeezed states and a nonlinear readout further allows for an N−3/2 precision scaling, which we prove is asymptotically optimal. We also show how to counter noise-induced bias by introducing a simple ratio estimator, which relies on detecting two suitable system observables, and we show that it remains asymptotically unbiased in the presence of dephasing, without detriment to the achievable precision.